Z polityki brytyjskiej wobec Hiszpanii. Wyspy Zielonego Przylądka, Azory i Wyspy Kanaryjskie w planach Gabinetu Wojennego Winstona S. Churchilla (1940–1941) - Kaczorowski, Bartosz (Acta Universitatis Lodziensis. Folia Historica, 2012)
Although Spain did not participate in the World War II, it played an important role in the politics of the United Kingdom. The main reason of this fact was a menace that general Francisco Franco would decide to join the war on the Axis side and attack Gibraltar – a gate to the Mediterranean Sea. Even though many actions were taken in order to maintain and reinforce Spanish neutrality, Great Britain decided to prepare some alternative solutions in case of the failure of diplomatic efforts. Supposing that the loss of the Rock was inevitable, the British military command created plans of occupation of Spanish Canary Islands (operation Puma) and Portuguese Azores (Operation “Pilgrim”) and Cape Verde Islands (Operation “Shrapnel”) that could serve as a naval base in the vicinity of Gibraltar. To what extend were these military conclusions taken into consideration by Winston Churchill’s War Cabinet and what consequences could it bring to the United Kingdom if they were executed? This article is an attempt to give answers to these questions.